2015
DOI: 10.1007/s10549-015-3379-2
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma and atypical vascular lesions of the breast: diagnostic and prognostic role of MYC gene amplification and protein expression

Abstract: MYC amplification has been reported as a prominent feature of secondary angiosarcomas (SAS). The differential diagnosis between atypical vascular lesion (AVL) and low-grade angiosarcoma (AS) can be occasionally very difficult or even impossible, and MYC amplification status has been pointed as an important diagnostic tool to distinguish cutaneous vascular lesions of the breast. We assessed MYC amplification and protein expression status by fluorescent in situ hybridization (FISH) and immunohistochemistry (IHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 26 publications
1
66
0
Order By: Relevance
“…Finally, MYC is a well-known transcription factor that plays a central role in cancer development processes including cell proliferation, growth, and apoptosis. MYC has been previously upregulated in cases of radiation-induced angiosarcoma (40, 41) and glioblastoma, with its expression associated with longer overall survival (42) but here we see a strong and consistent downregulation in all endometrial cancer patients after radiotherapy.…”
Section: Discussionsupporting
confidence: 56%
“…Finally, MYC is a well-known transcription factor that plays a central role in cancer development processes including cell proliferation, growth, and apoptosis. MYC has been previously upregulated in cases of radiation-induced angiosarcoma (40, 41) and glioblastoma, with its expression associated with longer overall survival (42) but here we see a strong and consistent downregulation in all endometrial cancer patients after radiotherapy.…”
Section: Discussionsupporting
confidence: 56%
“…Sorafenib, a multi‐targeted tyrosine kinase inhibitor of RAF, VEGF 1‐3, PDGFRβ, FLT‐3, RET, and c‐KIT, was studied by the SWOG intergroup in a phase II (S0505) trial in advanced soft tissue sarcoma: no confirmed response was observed in the 37 patients, and the study was closed prematurely . Amplification of MYC is a feature of RAAS seen in 54% of cases . MYC amplification can be assessed by FISH or immunohistochemistry, which can aid in differentiating RAAS from the benign entity of atypical vascular lesion where MYC is not overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate that MYC protein expression in AS appears to be helpful in the differential diagnosis of AVL and AS in the breast but not in other sites. Also, it appears that MYC is not entirely specific for secondary AS, as was originally suggested; because a rare subset of primary AS (UV‐related) may also show MYC amplification.…”
Section: Introductionmentioning
confidence: 92%
“…Such ancillary studies may be of aid in some cases for arriving at the correct diagnosis, particularly on limited biopsies or if the biopsy is taken from the periphery of the lesion. However, it is important to note that MYC amplification is not detected in all cases of secondary AS, particularly the well‐differentiated examples which are more prone to confusion with AVL; thus, lack of expression would not exclude AS . Some authors have indicated that secondary AS with MYC amplification have worse prognosis compared to cases without this molecular abnormality .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation